Preparação e caracterização de compósitos de polianilina (DMcT Cu(II)) / fibra de carbono como catodos em baterias secundárias - Canobre, Sheila Cristina (2004)
The composites were obtained by cyclic voltammetry and the incorporation of Cu(II) to the Pani(DMcT) / C fiber composite was carried out by two methods: A) Cu(II) added to the polymerization electrolyte along with the aniline, and B) Cu(II) and DMcT adsorbed onto the carbon fiber for 12 h, in a step previous to the electropolymerization. The comparison of complex-plane diagrams obtained at 0.2 V for the composites prepared by method B and for the pure poli(DMcT) film showed that the values of the charge transfer resistance are significantly smaller for the composites; on the other hand, at 0.2 V the composites presented greater pseudocapacitance values than the pure poli(DMcT) film due to their porous and homogeneous morphology. The experimental discharge capacity for this composite in 1 M LiClO4 in propylene carbonate was 110 mA h g-1, with a coulombic efficiency of 100%, and 165 mA h g-1 in a jellified polymeric electrolyte (κ = 1,8.10-3 S cm-1), with a coulombic efficiency of 100% after 20 charge/discharge cycles, indicating that both materials (Pani and poli(DMcT)) remained active during the charge and discharge processes. The good stability and reversibility characteristics of the redox reactions of this composite are due to the presence of Cu(II) and the sulfur of the thiol group, which were detected by XPS. The discharge capacities of the bilayer Ppy- PSS- / Pani / C fiber and Pani / Ppy-PSS- / C fiber electrodes, obtained after 20 cycles in the charge and discharge tests, were approximately 225 mA h g-1, with a coulombic efficiency of 100%, and 60 mA h g-1, with a coulombic efficiency of 29%, respectively. Once the cathode (obtained by method B) and anode (Ppy-PSS- / Pani / C fiber) materials were chosen, along with the polymeric electrolyte analyzed, the main objective of this thesis project became feasible: realization of charge and discharge tests of a battery made only of polymeric materials (cathode, anode and electrolyte). The cell potential of this battery was only 0.68 V, which lead to the low value of the energy density of 148 W h g-1. However, the battery presented a high initial value of the discharge capacity, 129 mA h g-1, after 3 cycles, with a coulombic efficiency of about 100%.